Cervical cancer and human papillomavirus vaccine knowledge, utilisation, prevention educational interventions and policy response in Nigeria: a scoping review (2022)
Purpose: This review evaluated the knowledge, utilisation, prevention education, and policy response across the six geopolitical regions of Nigeria to inform national efforts for the prevention and control of cervical cancer. Methods: A keyword-based systematic search was conducted in PubMed/MEDLINE (NCBI), Google Scholar, and AJOL electronic databases, including a manual scan of papers, journals and websites to identify relevant peer-reviewed studies. Articles were screened and assessed for eligibility. Results: Many (158) articles were downloaded and after duplicates were removed, 110 articles were included in the final analysis. These were made up of qualitative, quantitative (cross-sectional), intervention and policy studies. Studies have generally reported poor knowledge and awareness of cervical cancer screening but those carried out in urban areas demonstrated a slightly higher level of awareness of Human Papilloma Virus (HPV) vaccine, HPV vaccination uptake and utilization of cervical cancer preventive services than the rural studies. The studies did not show strong government support or policies in relation to cervical cancer control. Conclusion: Knowledge and uptake of cervical cancer preventive services across diverse groups in Nigeria remain poor. These could be linked to socio-cultural factors, the lack of an organised cervical cancer screening programme and low financial resource pool for cervical cancer prevention. Therefore, it is necessary to increase government, donor prioritisation and political support in order to ensure increased investment and commitment to cervical cancer elimination in Nigeria.